What is the importance of measuring heart rate and lactate levels in tennis players? - Therminarias, A.; Dansou, P. (1999)
The heart rate, registered during practice or in the course of a match, varies according to the duration and intensity of the rallies and the level and the style of play. It increases rapidly during rallies, sometimes approaching the maximal heart rate if the ball exchange is fast and prolonged. In the break between two rallies it slows down again, but does not really decerase until the players change ends. In experienced players, the average calculated heart rate (including breaks) is more than 60% of the maximum heart rate, and in difficult matches more than 80%. In veteran players, with a diminution of maximal heart rate, this percentagte is usually higher. In prolonged matches, however, the heart rate level may progressively increase, with values close to maximum at the end of the match. This augmentation is a result of elevated heart rate levels during rallies, but also during the change of ends. Slower recuperation is observed in veterans and is enhanced by dehydration. Simultaneous registrations of heart rate and oxygen consumption in 10 players during a match have shown an astonishing resemblance in the evolution of the graphs. Like heart rate, oxygen consumption augments rapidly when the ball is in play, diminishing again during breaks, and does not really decrease until the change of ends. Heart rate measurements therefore provide a good indication of players' aerobic energy expenditure. Lactate levels also vary according to the conditions of play. Blood lactate levels during a match usually remain below 4 mmol/L. Levels may be elevated for a period of 2-3 minutes, but decrease again quickly in the course of a match. The lactate level reflects the contribution of anaerobic metabolism to total energy consumption. This contribution is generally moderate, depending on the layer's lactate threshold. Measuring player's heart rates may be useful to determine their oxygen consumption during play, to compare this to their maximal oxygen consumption and, if necessary, to develop their power through an adequate training program. Measuring lactate levels may help players to gain more insight into the metabolic pathways used during play, as a function of their aerobic capacity and type of play.